2021
DOI: 10.33546/bnj.1702
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between quality of work-life, resilience and burnout among nursing professionals during COVID-19 pandemic in Iran: A cross-sectional study

Abstract: Background: The COVID-19 pandemic and the increased workload and stress associated with the disease prevalence have posed a high risk of burnout to nurses. The effects of the workplace and environmental factors on resilience and burnout among nursing professionals have not been investigated in Iran. Objective: Present study aimed to assess a model linking quality of work-life to the resilience and various dimensions of burnout among Iranian nursing professionals based on the health service workplace envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 44 publications
(62 reference statements)
0
26
0
3
Order By: Relevance
“…The study found explaining the factors associated is the most significant variable that harms QNWL and affects burnout as well, namely workload, control, community, rewards, fairness, values, and work environment (1,4,(9)(10)(11)(12)22,23), is also determined by the interaction between risk factors (e.g., symptoms of depression/ bullying and anxiety) and protective factors (e.g., good social support) (10,13,24). The sociodemographic variables associated with QNWL and Burnout are age, finances, education, gender, marital status, having children, personality, and expectations and shift work (10,14,21,22,(25)(26)(27)(28).…”
Section: Factors Associated With Qnwl and Burnoutmentioning
confidence: 93%
See 4 more Smart Citations
“…The study found explaining the factors associated is the most significant variable that harms QNWL and affects burnout as well, namely workload, control, community, rewards, fairness, values, and work environment (1,4,(9)(10)(11)(12)22,23), is also determined by the interaction between risk factors (e.g., symptoms of depression/ bullying and anxiety) and protective factors (e.g., good social support) (10,13,24). The sociodemographic variables associated with QNWL and Burnout are age, finances, education, gender, marital status, having children, personality, and expectations and shift work (10,14,21,22,(25)(26)(27)(28).…”
Section: Factors Associated With Qnwl and Burnoutmentioning
confidence: 93%
“…The study found explaining the definition of QNWL is defined as the ability of employees to meet their important personal needs while also achieving organizational goals is important element nurses possess and can affect the quality of health services provided to patients (1,12,(16)(17)(18)(19).…”
Section: Definitions Of Qnwl and Burnout Of Reviewed Studiesmentioning
confidence: 99%
See 3 more Smart Citations